Residu Fungisida Tembaga (Cu) pada Pucuk Teh - Christanti Sumardiyono (Universitas Gadjah Mada, 1996)
The study was done to know copper residue on tea due to blister blight control by copper fungicides. The experiment was done at Pagilaran Tea Plantation, Batang, Pekalongan. Tea plants were sprayed 8 times, with 8 days interval at the dosages of 0. 75, 150, and 300 g/ha respectively. Shoot sample was taken at 8 and 16 days after spraying. The copper residue war analyzed by Atomic Adsorbtion Spectrophotometer at 324 nm. The result showed that the higher dosage of spraying gives higher copper residue. At the dosage of 300 g/ha was detected 23,52 ppm of copper residue at 8 days after spraying. The residue was reduced to 12,96 ppm at 16 days after spraying. At that dosage the blister blight disease intensity reduced by 59,97%. The detected residue of copper fungicides due to blister blight control is not higher than MRL ( 150 ppm).